2018
DOI: 10.1002/ece3.4598
|View full text |Cite
|
Sign up to set email alerts
|

Orchid diversity: Spatial and climatic patterns from herbarium records

Abstract: AimWe test for spatial and climatic patterns of diversification in the Orchidaceae, an angiosperm family characterized by high levels of species diversity and rarity. Globally, does orchid diversity correlate with land area? In Australia, does diversity correlate with herbarium collecting effort, range size, or climate niche breadth? Where are Australia's orchids distributed spatially, in protected areas, and in climate space?LocationGlobal, then Australia.MethodsWe compared orchid diversity with land area for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 69 publications
2
21
0
Order By: Relevance
“…Research carried out in the Slovak Republic and other countries confirms that significant factors of distribution are the geological conditions of the area, which has a considerable impact on their occurrence and overall phytogeographical distribution of these species, as well as indicative values of populations, their communities and spatio-temporal changes in occurrence; these claims can be defined on the basis of the relationship to the environment and the influence of environmental factors. Similar research has been carried out in the Western Carpathians [ 6 ] and in Europe by several authors [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionsupporting
confidence: 66%
“…Research carried out in the Slovak Republic and other countries confirms that significant factors of distribution are the geological conditions of the area, which has a considerable impact on their occurrence and overall phytogeographical distribution of these species, as well as indicative values of populations, their communities and spatio-temporal changes in occurrence; these claims can be defined on the basis of the relationship to the environment and the influence of environmental factors. Similar research has been carried out in the Western Carpathians [ 6 ] and in Europe by several authors [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionsupporting
confidence: 66%
“…There are approximately 29,000 orchid species on all continents except Antarctica with a variety of life forms, from terrestrial to epiphytic (Givnish et al 2016). Many orchid species are local endemics and their distributions are constrained by edaphic environments and by their relationships with mycorrhizal fungi and specialist pollinators (McCormick & Jacquemyn 2014;Gaskett & Gallagher 2018). Orchids are economically important in horticulture and in the floral, pharmaceutical, and food industries (Subedi et al 2013;Hinsley et al 2018) and many species face immediate threats by land conversion and illegal harvesting (Hinsley et al 2017;Fay 2018).…”
Section: Introductionmentioning
confidence: 99%
“…These centers of orchid extinction risk coincide well with known areas of endemism, and hence small range sizes, for all plants (Kier et al 2009). The North American Orchid flora is surprisingly depauperate given its large area (Gaskett & Gallagher 2018), and we found that few species in this region are Possibly Threatened (Fig. 1, Fig.…”
Section: Orchid Extinction Riskmentioning
confidence: 71%
“…There are approximately 29,000 orchid species (Givnish et al 2016) on all continents except Antarctica with a variety of life forms, from terrestrial to epiphytic (Cribb et al 2003;Givnish et al 2016). Many orchid species are local endemics and their distributions are constrained by edaphic environments and by their relationships with mycorrhizal fungi and specialist pollinators (McCormick & Jacquemyn 2014;Gaskett & Gallagher 2018). Orchids are economically important in horticulture and in the floral, pharmaceutical, and food industries (Subedi et al 2013;Hinsley et al 2018) and many species face immediate threats by land conversion and illegal harvesting (Hinsley et al 2017;Fay 2018).…”
Section: Introductionmentioning
confidence: 99%